Oriented Fiberboard (OSB) - Abdullayev Ikrom Aminjanovich (Genius Journals, 2024)
Oriented fiber covering materials are panels made of wood chips. Its abbreviation is derived from the initials of the English phrase "Oriented Strand Board", which means "oriented particle board" when translated. means bread.
Keywords: Wood; layer; coating; mold